Design ethnography - Pink, Sarah, author.
1 online resource
Keywords: "This book advances the practice and theory of design ethnography. It presents a methodologically adventurous and conceptually robust approach to interventional and ethical research design, practice, and engagement. The authors, specialising in design ethnography across the fields of anthropology, sociology, human geography, pedagogy, and design research, draw on their extensive international experience of collaborating with engineers, designers, creative practitioners, and specialists from other fields. They call for, and demonstrate the benefits of, ethnographic and conceptual attention to design as part of our personal and public everyday lives, society, institutions, and activism. Design Ethnography is essential reading for researchers, scholars and students seeking to reshape the way we research, live, and design ethically and responsibly into yet unknown futures"--